Emerging rechargeable aqueous aluminum ion battery : status, challenges, and outlooks - Yuan, Du (2021)
Aluminum ion battery (AIB) technology is an exciting alternative for post-lithium energy storage. AIBs based on ionic liquids have enabled advances in both cathode material development and fundamental understanding on mechanisms. Recently, unlocking chemistry in rechargeable aqueous aluminum ion battery (AAIB) provides impressive prospects in terms of kinetics, cost, safety considerations, and ease of operation. To review the progress on AAIB, we discuss the critical issues on aluminum electrochemistry in aqueous system, cathode material design to overcome the drawbacks by multivalent aluminum ions, and challenges on electrolyte design, aluminum stripping/plating, solid-electrolyte interface (SEI) formation, and design of cathode materials. This review aims to stimulate exploration of high-performance AAIB and rationalize feasibility grounded on underlying reaction mechanisms.